2013
DOI: 10.1007/s11999-012-2631-x
|View full text |Cite
|
Sign up to set email alerts
|

Poor Long-term Clinical Results of Saddle Prosthesis After Resection of Periacetabular Tumors

Abstract: Reconstruction with saddle prostheses after periacetabular tumor surgery has a high risk of complications and poor long-term function with limited hip flexion; therefore, we no longer use the saddle prosthesis for reconstruction after periacetabular tumor resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
95
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 30 publications
(99 reference statements)
4
95
1
5
Order By: Relevance
“…The potential specific complications related to this procedure may include infection, skin necrosis, hematoma, abdominal hernia, fracture, postoperative pain, accelerated osteoarthritis, and postoperative hip dislocation. The complication rate was quite high in the conventional reconstruction [16,22]. In a series of 17 saddle prosthesis reconstructions, there were 14 local complications including infection, dislocation, and limb length discrepancy [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential specific complications related to this procedure may include infection, skin necrosis, hematoma, abdominal hernia, fracture, postoperative pain, accelerated osteoarthritis, and postoperative hip dislocation. The complication rate was quite high in the conventional reconstruction [16,22]. In a series of 17 saddle prosthesis reconstructions, there were 14 local complications including infection, dislocation, and limb length discrepancy [16].…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate was quite high in the conventional reconstruction [16,22]. In a series of 17 saddle prosthesis reconstructions, there were 14 local complications including infection, dislocation, and limb length discrepancy [16]. For the allograft reconstruction, there was 28% infection [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we performed surgery in patients with many co-morbidities (four patients classified as ASA 4) with extended, generalised metastatic disease we had no intra-or postoperative deaths and observed no major complications such as excessive haemorrhage, deep infections, lesions of the femoral nerve, loss of fixation, or dislocations as described in other series after performing various methods for pelvic reconstruction [9,14,15,[17][18][19]. Tillman et al have reported similar results in their series of 19 patients treated with a three-pin modified Harrington technique with respect to occurrence of major intra-and postoperative complications as well as the functional outcome [6].…”
Section: Discussionmentioning
confidence: 90%
“…Renard et al noted that osteoporosis and insufficient soft tissue quality have affected the functional results in a series of 15 patients treated with saddle prosthesis for periacetabular tumours [14]. A recent study by Jansen et al reported a high risk of complications and poor long-term function in patients following acetabular reconstruction with saddle prostheses after peri-acetabular tumour surgery [15]. Another technique of endoprosthetic restoration, especially in relation to reconstruction of extended pelvic defects in cases of primary malignant tumours or solitary metastatic bony lesions of the pelvis, is the internal hemipelvectomy and reconstruction with an endoprosthetic pelvic replacement [9,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%